1999
DOI: 10.1038/sj.bjp.0702678
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously hypertensive rats cholinergic hyper‐responsiveness: central and peripheral pharmacological mechanisms

Abstract: 1 The mechanisms and the subtypes of muscarinic receptors implicated in the cardiovascular eects of physostigmine were investigated in conscious normotensive and spontaneously hypertensive rats. 2 Intravenous (i.v.) physostigmine (50 mg kg 71) induced in both strains a long pressor response, accompanied by a bradycardia. This pressor response was larger in spontaneously hypertensive (+41+6 mmHg) than in Wistar-Kyoto (+25+2 mmHg) rats (P50.05). 3 Pretreatment with atropine sulphate (0.4 mg kg 71 i.v.), complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In the study conducted by Lazartigues et al (1999), increases in HR were observed in the WKY, but not in the SHR.…”
Section: Does T Violacea Act By Blocking the Beta I Adrenoceptors?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Lazartigues et al (1999), increases in HR were observed in the WKY, but not in the SHR.…”
Section: Does T Violacea Act By Blocking the Beta I Adrenoceptors?mentioning
confidence: 99%
“…In literature, muscarine (a parasympathomimetic agent) has been reported be have activity similar to that of acetyl choline, although being more potent. Previous reports in literature alludes to the fact that muscarine reduces BP, while atropine (a parasympatholytic agent) has been reported in literature to have various effects on BP; from increases (Bartholow, 1908;Fraser, 1957;Wess et al, 1987), to no effect in WKY rats and SHR (Lazartigues et al, 1999;Mestivier et al, 2001), and to immediate and dose-dependent reductions, at the doses of 5-50 mg/kg given intravenously in conscious unanaesthetized WKY rats and hypertensive rats (SHR, and Sprague-Dawley rats made hypertensive by subcutaneous implantation of deoxycorticosterone acetate) (Abraham et al, 1981a(Abraham et al, , 1981bCantor et al, 1983).…”
Section: Does T Violacea Act By Blocking the Beta I Adrenoceptors?mentioning
confidence: 99%
“…Potential cardiac effects are also important and have been examined in a limited number of animal studies, which demonstrate bradycardia and atrioventricular block due to the potentiation of parasympathetic nervous control (mediated through the vagus nerve). (James et al, 1979;Lazartigues et al, 1999) Despite this risk, electrocardiogram monitoring has not been routinely performed in pre-clinical studies investigating nerve agent pre-treatment. Coadministration with competitive muscarinic receptor antagonists (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although additional experiments are still necessary to identify whether Bj-PRO-7a acts or not on any further metabotropic receptors or ion channels, this work provides a novel tool for investigation of mAChRs in addition to potential therapeutic applications of this natural peptide. Finally, the characterization of Bj-PRO-7a as M1 receptor agonist brings new insights to explain the antihypertensive actions of this peptide family (23), which was shown to be not fully explained by ACE inhibition.…”
Section: Brief Reportmentioning
confidence: 99%
“…Five subtypes of mAChRs (M1-M5) belonging to the superfamily of G-protein-coupled receptors mediate the effects of acetylcholine by central and peripheral cholinergic neurotransmission, including on blood pressure control (22). In this context, Lazartigues et al (23) suggested that modifications in M1 muscarinic receptors could be at the origin of hyper-responsiveness of a hypertensive rat strain to cholinergic drugs. Moreover, altered cardiovascular responses were observed in M1 mAChR knock-out mice (24).…”
mentioning
confidence: 99%